2015
DOI: 10.1111/pre.12093
|View full text |Cite
|
Sign up to set email alerts
|

Squishy lipids: Temperature effects on the betaine and galactolipid profiles of a C18/C18 peridinin‐containing dinoflagellate, Symbiodinium microadriaticum (Dinophyceae), isolated from the mangrove jellyfish, Cassiopea xamachana

Abstract: Summary Previous work from our laboratory has shown dinoflagellates, which possess the carotenoid peridinin, have been divided into two clusters based on plastid galactolipid fatty acid composition. In one cluster major forms of monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), lipids that comprise the majority of photosynthetic membranes, were C18/C18 (sn‐1/sn‐2), with octadecapentaenoic [18:5(n‐3)] and octadecatetraenoic [18:4(n‐3)] acid as principal fatty acids. The other cluster co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
4
32
0
Order By: Relevance
“…Both 28:7 and 28:8 acids were found only in the fraction of phospholipids, not in glycolipids (Leblond and Dahmen, 2012) such as MGDG, DGDG, and SQDG, which, on the contrary, contained 18:4 and 18:5 with the major molecular species 18:4/18:5-MGDG and 18:4/18:5-DGDG (Leblond et al, 2015). These findings indicate that the C28 fatty acids are located and probably synthesized in the cytoplasm or in an organelle other than the chloroplast, whereas the C 18 fatty acids e 18:4n-3 and 18:5n-3 -are glycolipid constituents apparently synthesized within the chloroplast.…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 91%
See 1 more Smart Citation
“…Both 28:7 and 28:8 acids were found only in the fraction of phospholipids, not in glycolipids (Leblond and Dahmen, 2012) such as MGDG, DGDG, and SQDG, which, on the contrary, contained 18:4 and 18:5 with the major molecular species 18:4/18:5-MGDG and 18:4/18:5-DGDG (Leblond et al, 2015). These findings indicate that the C28 fatty acids are located and probably synthesized in the cytoplasm or in an organelle other than the chloroplast, whereas the C 18 fatty acids e 18:4n-3 and 18:5n-3 -are glycolipid constituents apparently synthesized within the chloroplast.…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 91%
“…Betaine lipids such as diacylglycerylcarboxy-Nhydroxymethylcholine (DGCC) were found to contain highly unsaturated molecular species of the types 44:15-and 46:15-DGCC (Flaim et al, 2014) or 44:12-DGCC (Leblond et al, 2015) while diacylglyceryltrimethyl-homoserine (DGTS) was found to contain only saturated and monoenoic species, e.g. 32:1-DGTS (Leblond et al, 2015).…”
Section: Separation and Identification Of Lipid Classesmentioning
confidence: 99%
“…To our knowledge, there have been no studies regarding the lipid content of this taxon and how this may relate to thermal niche. However, the effects of temperature on fatty acids composition patterns have been addressed by some studies on micro-(e.g., FuSChino et al 2011;Flaim et al 2012;Leblond et al 2015) and macroalgae (e.g., BeCKer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high abundance of DHA in Symbiodinium phylotypes and in other flagellate microalgae (Leblond et al, 2000(Leblond et al, , 2006(Leblond et al, , 2015Gray et al, 2009;Awai et al, 2012;Armada et al, 2013;Dahmen et al, 2013;Anesi & Guella, 2015;Anesi et al, 2016) sustains the idea proposed by Valentine (2009): phytoplankton represents the global stock of DHA production in the marine ecosystem. Life cycle of zooplankton species depend on the nutritional quality of phytoplankton, which is defined by lipid content (Søreide et al, 2010).…”
Section: Importance Of Phytoplankton Lipids In the Global Carbon Budgmentioning
confidence: 90%
“…For example, a great diversity of glyco and amino membrane lipids in Symbiodinium spp. and other dinoflagellates has been described by LC-MS analysis, including few alterations when growing in distinct temperatures (Leblond et al, 2000(Leblond et al, , 2006(Leblond et al, , 2010(Leblond et al, , 2015Gray et al, 2009;Dahmen et al, 2013;Flaim et al, 2014;Anesi et al, 2015Anesi et al, , 2016. These studies were mostly focused on a specific class of polar lipid such as glycolipids or aminolipids, and not aimed at characterizing the global lipidome together with specialized lipids, such as plastoquinone and pigments using LC-MS.…”
Section: Lipidomics As Tool To Better Characterize Microalgae Lipidsmentioning
confidence: 99%